Synthetic and structural investigation into homo- and hetero-, di- and tri-nuclear complexes containing osmium - Sutton, Elizabeth Eldred (Department of Chemistry, 2016)
Chain cluster complexes have been largely neglected in the general discussion on metal cluster complexes. The first chapter of this thesis has been devoted to an updated review of the synthetic and structural aspects of chain cluster complexes, classifying species of this type in a group of their own, as a sub - set of the large class of compounds loosely referred to as metal cluster complexes. The reaction of Os₃(CO)₁₂ with X₂ (X = Cl, Br or I) in benzene, in direct, bright sunlight or a Hanovia photo-chemical reactor, has been studied. The nature of the products of the reactions depends critically on the experimental conditions employed. Os2(CO)₈X₂ (X = Br or I), among other products, are obtained in reasonable yield, directly from Os₃(CO)₁₂. (Os₂(CO)₆I₂ has been prepared from Os₂(CO)₈I₂ in 80% yield and the reactivity of the hexa-carbonyl derivative with CO, PPh₃, PMe₂Ph, I3, H₂ and C₂H₄ has been studied. The new species, Os2(CO)₆(PPh₃)₂I₂ and Os2(C0)₆(PMe₂Ph)₂I₂, are obtained. Cis-Os(CO)₄X₂ (X = Cl, Br or I) are thermally converted into Os₂(CO)₆X₄ (X = Cl, Br or I) species.